The Radboud Biobank: A Central Facility for Disease-Based Biobanks to Optimise Use and Distribution of Biomaterial for Scientific Research in the Radboud University Medical Center, Nijmegen. (6th February 2018) - Manders, Peggy; Lutomski, Jennifer E.; Smit, Cees; Swinkels, Dorine W.; Zielhuis, Gerhard A.
The Radboud Biobank offers disease-based biobanks a centralized facility to optimize the use and distribution of biomaterial for scientific research. Notably, two population biobanks are also included in this collection. All collections are professionally and sustainably maintained using high-quality and secure standardized protocols for ICT, legal-ethical aspects, sample collection, processing and storage, communication and distribution. The Radboud Biobank includes biomaterial (e.g. DNA, serum, plasma, tissue, urine and faeces – depending on the specific patient group), images, associated clinical data (patient, disease-specific and phenotypic data) and derived information (genotypic data, microarray gene expressions). Patient advocates and other relevant stakeholders are actively involved in the governance of the Radboud Biobank.